Structure and performance analysis of binary differential stochastic process shift keying - Zhi-jiang XU; Xiao LING; Kang WANG; Li-min MENG (Tongxin xuebao)
A novel modulation and demodulation structure based on binary differential stochastic process shift keying (BDSPSK) is proposed.The theoretical bit error rates (BER) under the Gaussian and quasi-static Rayleigh fading chan-nels are derived,respectively.To verify its performances and security,lots of simulations are done by using MATLAB.The simulations' results show that the BER of the proposed BDSPSK can reach 10−4when signal to noise ratio (SNR) is about −2 dB in the Gaussian channel or 25 dB in the Rayleigh fading channel.Meanwhile,the proposed method has a good concealment due to its undetectable property by the generalized second order cyclostationary spectrum,which makes it suit for secure communications in the physical layer.